FINANCIAL, TAX LITERACY, CAPITAL STRUCTURE, PERFORMANCE AND COMPETITIVENESS OF MSMEs IN THE DIGITAL TRANSFORMATION ERA - Antoni, Antoni (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Conclusion can be drawn that Micro, Small, and Medium Enterprises (MSMEs) were prioritized in every country’s development agenda. This was due to the significant contributions of MSMEs to the economy and society. Besides driving economic growth, MSMEs played a crucial role in providing employment opportunities, particularly in the informal sector, and distributing income, especially in regional areas. The main challenges faced by MSMEs in Indonesia were internal constraints. Bank Indonesia states that internal constraints encompass capital, human resources, legal matters, and accountability issues. Additionally, external constraints identified by Bank Indonesia (2015) included the business climate, infrastructure, and resource access. To support the development and competitiveness of existing MSMEs, both the internal and external constraints should be addressed with the assistance of the government. The significance of financial literacy for MSMEs, as well as individuals, cannot be understated. It is a fundamental requirement for effective and efficient financial management. MSMEs in the culinary sector faced uncertainties in maintaining business continuity due to limited internal resources, challenges in customer communication, technology limitations, and intense competition from new market entrants. Therefore, for MSMEs, ensuring the sustainability of their businesses was of utmost importance. Several factors, including financial literacy, technological literacy, and innovation, played crucial roles in determining their success.